Multi-Omics Analyses Reveal the Regulatory Network and the Function of ZmUGTs in Maize Defense Response - Ge, Chunxia; Wang, Yi-Ge; Lu, Shouping; Zhao, Xiang Yu; Hou, Bing-Kai; Balint-Kurti, Peter J.; Wang, Guan-Feng (Frontiers in Plant Science, 2021)
Maize is one of the major crops in the world, however, diseases caused by various pathogens seriously affect its yield and quality. The maize Rp1-D21 mutant caused by the intragenic recombination between two nucleotide-binding, leucine-rich repeat proteins, exhibits autoactive hypersensitive response (HR). In this study, we integrated transcriptomic and metabolomic analyses to identify differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs) in Rp1-D21 mutant compared to wild type. Genes involved in pathogen-associated molecular pattern-triggered immunity and effector-triggered immunity were enriched among the DEGs. The salicylic acid (SA) pathway and the phenylpropanoid biosynthesis pathway were induced at both the transcriptional and metabolic levels. The DAMs identified included lipids, flavones and phenolic acids, including 2,5-DHBA O-hexoside, the production of which is catalyzed by uridine diphosphate (UDP)-dependent glycosyltransferase (UGT). Four maize UGTs (ZmUGTs) homologous genes were among the DEGs. Functional analysis by transient co-expression in Nicotiana benthamiana showed that ZmUGT9250 and ZmUGT5174, but not ZmUGT9256 and ZmUGT8707, partially suppressed the HR triggered by Rp1-D21 or its N-terminal coiled-coil signaling domain (CCD21). None of the four ZmUGTs interacted physically with CCD21 in yeast two-hybrid or co-immunoprecipitation assays. We discuss the possibility that ZmUGTs might be involved in defense response by regulating SA homeostasis.